Miller Fisher variant of Guillain Barre Syndrome: A Case Report (Faridpur Medical College Journal, 2016)
Miller Fisher Syndrome (MFS) is characterized by acute onset of ophthalmoplegia, ataxia and loss of tendon reflexes with relative sparing of strength in the extremities and trunk. Our patient Mr. Akter Sheikh, 40 years male, non diabetic, non hypertensive, presented with generalized weakness and difficulty in walking for 7 days preceded by a history of respiratory tract infection. After clinical and CSF examination, he was diagnosed as a case of Miller-Fisher syndrome. With treatment he improved significantly.Faridpur Med. Coll. J. Jan 2015;10(1): 44-45